Mild to moderate drought stress reinforces the role of functional microbiome in promoting growth of a dominant forage species (Neopallasia pectinata) in desert steppe - Gao, Hui; Huang, Zhenzhen; Chen, Weiwei; Xing, An; Zhao, Shixiang; Wan, Weifan; Hu, Haina; Li, Haigang (Frontiers in Microbiology, 2024)
Background: Desert steppe ecosystems are prone to drought stress, which influences the ecological balance and sustainable development of grasslands. In addition to directly restrict plant growth, drought stress indirectly impacts plant fitness by altering the diversity and function of root-associated microbiomes. This begs the question of whether the functional microbiome of forage plants, represented by synthetic microbial communities (SynComs), can be leveraged to mitigate drought stress in desert steppes and promote the ecological restoration of these fragile ecosystems.A pot experiment was conducted to evaluate the role of SynComs in improving the plant growth and drought stress resistance of Neopallasia pectinata (Pall.) Poljak in desert steppe in Inner Mongolia, China. Six SynComs were derived from the rhizosphere and root endosphere of 12 dominant forage species in the desert steppe. Each SynCom comprised two to three bacterial genera (Bacillus, Protomicromonospora, and Streptomyces. We examined the capacities of different SynComs for nutrient solubilization, phytohormone secretion, and enzymatic activity.Results: Under no water stress (75% soil water holding capacity, WHC), single strains performed better than SynComs in promoting plant growth in terms of stem diameter, root length, and plant dry weight, with the greatest effects observed for Streptomyces coeruleorubidus ATCC 13740 (P < 0.05).However, under mild to moderate drought stress (55% and 35% WHC), SynComs outperformed single strains in enhancing plant biomass accumulation and inducing the production of resistance-related substances (P < 0.05). No significant effect of single strains and SynComs emerged under extreme drought stress (20% WHC). Conclusions: This study underscores the potential of SynComs in facilitating forage plants to combat drought stress in desert steppe. Mild to moderate drought stress stimulates SynComs to benefit the growth of N. pectinata plants, despite a soil moisture threshold (21% WHC) exists for the microbial effect. The use of SynComs provides a promising strategy for the ecological restoration and sustainable utilization of desert steppes by manipulating the functional microbiome of forage plants.